Manipulative Maneuvers: A Comparative Study ofOthello and King Lear (Journal of Asian Development Studies, 2024)
William Shakespeare is famous for the universality and uniqueness of his plays. Most of thecharacters that he portrays are life-like. In most of his plays, he portrays some manipulativecharacters who cunningly ruin the lives of the people around them. People trust, love, and admirethem, but in response, these manipulative persons exploit them to achieve their goals. Othello(1603) and King Lear (1605) are two different tragic plays written by Shakespeare, and both havemanipulative characters, i.e., Iago in Othello and Edmond in King Lear. They have been analyzedin this study to discover Shakespeare's understanding of human nature as manipulative in societyand the meaningful similarities between them in light of the comparative contextualanalysis technique. The findings reveal Shakespeare's nuanced portrayal of manipulativecharacters, showcasing the parallel yet distinct paths taken by Iago in "Othello" and Edmund in"King Lear," highlighting their cunning tactics, societal impact, and the universal thread of humanmanipulation; the conclusion underscores Shakespeare's profound comprehension of the darkerfacets of human nature, depicting the intricate interplay of manipulation, trust, and societalinfluence within his tragic plays